2021
DOI: 10.1186/s11689-021-09376-z
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 screening testing in schools for children with intellectual and developmental disabilities

Abstract: Background Transmission of SARS-CoV-2 in schools primarily for typically developing children is rare. However, less is known about transmission in schools for children with intellectual and developmental disabilities (IDD), who are often unable to mask or maintain social distancing. The objectives of this study were to determine SARS-CoV-2 positivity and in-school transmission rates using weekly screening tests for school staff and students and describe the concurrent deployment of mitigation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 11 publications
0
15
0
1
Order By: Relevance
“…With that, we should also note that self-collected saliva samples may have limitations in some settings where MTS or anterior nasal swabs might be preferable. For small children or people with intellectual and developmental disabilities (IDD), the collection of saliva may require supervision or assistance ( 26 ). However, in a study with students and staff from six schools dedicated to children with IDD as the study population, investigators found that with the help of nurses and teachers, saliva samples could be collected from students for weekly testing ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With that, we should also note that self-collected saliva samples may have limitations in some settings where MTS or anterior nasal swabs might be preferable. For small children or people with intellectual and developmental disabilities (IDD), the collection of saliva may require supervision or assistance ( 26 ). However, in a study with students and staff from six schools dedicated to children with IDD as the study population, investigators found that with the help of nurses and teachers, saliva samples could be collected from students for weekly testing ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…For small children or people with intellectual and developmental disabilities (IDD), the collection of saliva may require supervision or assistance ( 26 ). However, in a study with students and staff from six schools dedicated to children with IDD as the study population, investigators found that with the help of nurses and teachers, saliva samples could be collected from students for weekly testing ( 26 ). In addition, for some people, especially those who are febrile or dehydrated, the saliva samples could be thick and stringy, hence adding difficulty and additional procedures for the laboratory staff to process the samples ( 27 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a qualitative study to understand how COVID‐19 affected the school experience for staff, families, and students, and the impact of a weekly SARS‐CoV‐2 screening testing program 6,17 . The Washington University Institutional Review Board approved this study.…”
Section: Methodsmentioning
confidence: 99%
“…Подчеркивают, что при наблюдении за контактными людьми этот тест может быть самостоятельной альтернативой [22]. Высокочувствительный молекулярный тест со слюной полезен при обследовании детей школьного возраста [23]. Исследование слюны представлено в качестве альтернативы при обследовании детей с инфекцией COVID-19 для поиска диагностических и прогностических маркеров [24].…”
Section: Pediatrician Schoolunclassified